Rationing of health care services to the elderly in the opinion of staff hospital emergency departments - Adamczyk, Mateusz; Jędrzejkiewicz, Bernadeta; Ogórek, Marlena Anna; Dobrowolska, Beata (Journal of Education, Health and Sport, 2018)
Abstract Introduction. Rationing of medical services is based on several rules, among which stand out the ethical rules. This means equal access to health care for everyone regardless of age, religion, gender or social status. Possible discrimination because of age is called ageism, which consists of resentment, making unjust and unfair judgment or abusive choices in relation to the elderly. Purpose of the work. The aim of this study was to investigate the views of staff of hospital emergency departments on the ethical aspects of the rationing of health care services to the elderly. Material and methods. The study was conducted in 2017 in a group of 60 nurses and 60 paramedics working in emergency departments Lublin province. Diagnostic survey method was used. The collected material was subjected to statistical analysis using the software SPSS IBM Statistic. Results. The age of the patient, in determining order of medical care, was important to 18.4% (n = 22) tested. For nurses, the criterion of age was statistically more significant than for paramedics (p <0.001). 91.7% (n = 110) of the test target considers guiding by the age by the assistance as unethical. For 90% (n = 108) the right of access to the services should be equal. At the same time, only 26.7% (n = 32) of respondents believe that all patients are treated equally. 55% (n = 66) admits that at least once in a lifetime gave first aid to a younger person (guided by the criterion of age). Substantially more often the aid was given by nurses (p <0.001). 51.7% (n = 62) of respondents sees the inferior treatment of the elderly. Statistically more often this state was observed by nurses (p = 0.003). Conclusions. According to respondents, access to health services should be equal for everyone. At the same time they admit that older patients are not treated on a par with the young person and it happens that the elderly receive help later. More than half of the respondents observed the phenomenon of discrimination against the elderly in the emergency departments. It manifests itself in greater impatience, contempt, and the stereotypical image of an elderly man as a person in need of companionship, conversation, interests and no medical assistance.